Postbuckling behaviour of graphene-reinforced plate with interfacial effect (Archives of Mechanics - Test, 2018)
The present study is aimed to study the postbuckling response of the graphene sheet (GS)-reinforced plate including the effect of van-der-Waals (vdW) bonding between GS and matrix. An equivalent solid fibre (ESF) containing GS and the interfacial region is modelled, and that are randomly dispersed into the matrix with the aid of the Boolean based random sequential adsorption (RSA) technique. The elastic constants of the nanocomposite are calculated by the FEM-based homogenization procedure. It is established that interphase zone, stacking and short GSs pose the negative effect on the elastic properties of nanocomposite and postbuckling strength of the GS-reinforced plate.